Implementation of Legal Quality Audit on Electronic Civil Trial Procedures (E-Court) - Tampubolon, Yunto Safarillo Hamonangan; Murwadji, Tarsisius; ., Sudaryat (Journal of Ecohumanism, 2024)
Currently, electronic court (e-court) systems are being implemented in several countries. The Supreme Court in Indonesia has also been adopted e-court for legal administration tasks, such as determining judicial panel compositions. A qualitative approach is proposed to explore the implementation itself. The concept and characteristics of the Special Legal Quality Audit System for electronic justice arrangements (E-court) encourage the realization of an effective and fair Civil Justice System. The concept in this context is a philosophical aspect that serves as the source of the Legal Quality Assurance Paradigm, including: defect-free (deficiency), customer satisfaction, and continuous improvement without end. This concept is elaborated in parameters that are measured or evaluated to determine the quality level and make improvements to increase the level of quality. The quality parameters used by the researcherinclude: product reliability, minimal cost, accessibility, security, service friendliness, systematicity, and keeping pace with global developments.